Cooling of lithium-ion battery using PCM passive and semipassive thermal system immersed in nanofluid - Bashar R. Qawasmeh; Mohammad Alrbai; Sami George (Energy Exploration & Exploitation)
This study introduces a novel comparative analysis of thermal management systems for lithium-ion battery packs using four LiFePO4 batteries. The research evaluates advanced configurations, including a passive system with a phase change material enhanced with extended graphite, and a semipassive system with forced water cooling. A key innovation lies in replacing water with a nanofluid in a single cold plate surrounded by a phase change composite, leveraging the superior thermal properties of nanoparticles. Further advancements are presented in a three-plate system and a complex-plate system, which employ modified cold plate designs and two-dimensional flow dynamics for enhanced cooling. Among these, the complex-plate system with nanofluid proved most effective, reducing the maximum temperature by 17.17% from 88.17 °C in the passive system to 73.03 °C, while extending the operational temperature threshold by 7.41%. Nanoparticles contributed to a 9.46% temperature reduction, highlighting their impact on thermal performance. Notably, the complex-plate system surpassed the three-plate configuration in efficiency, achieving superior cooling with lower pumping power requirements. This study emphasizes the novelty and practicality of integrating nanofluids and advanced cooling designs, setting a benchmark for optimizing lithium-ion battery thermal management systems.